Albert Weale, Geoffrey Pridham, Michele Cini, Dimitrious Konstadakopoulos, Martin Porter and Brendan Flynn, Environmental Governance in Europe. An Ever Closer Ecological Union?, Oxford: Oxford University Press, 2000,525 s., 90,00; Arthur Mol, Volkmar Lau - Michelsen, Johannes (Politica, 2001)
Albert Weale, Geoffrey Pridham, Michele Cini, Dimitrious Konstadakopoulos, Martin Porter and Brendan Flynn, Environmental Governance in Europe. An Ever Closer Ecological Union?, Oxford: Oxford University Press, 2000,525 s., 90,00; Arthur Mol, Volkmar Lauber and Duncan Liefferink (eds.), The Voluntary Approach to Environmental Policy. Joint Environmental Police-making in Europe, Oxford: Oxford University Press, 2000, 262 s., 70,00.